2008
DOI: 10.1016/j.chemosphere.2008.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet degradation of methyltins: Elucidating the mechanism by identification of a detected new intermediary product and investigating the kinetics at various environmental conditions

Abstract: The photodegradation of methyltins, as environmental pollutants, has scarcely been studied so far because of the shortage of rapid and sensitive speciation methods, even though they have very simple structures. The photodegradation of monomethyltin trichloride (MMT), dimethyltin dichloride (DMT) and trimethyltin chloride (TMT) was studied with our new developed HPLC-FPD hyphenated system, which enables rapid and sensitive detection of methyltins. The half-life times and kinetic rate constants of their degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Under these redox conditions, the surface oxidation of PVC is likely driven by the photochemical production of hydroxyl radicals. OTCs can be photodegraded via dealkylation to produce low-substituted species and finally inorganic tin . Only DMT and DBT were detected in the reaction solutions under different light conditions with an initially increasing and then decreasing trend of concentrations, while the total tin concentrations continuously increased within the experimental period (Figure ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Under these redox conditions, the surface oxidation of PVC is likely driven by the photochemical production of hydroxyl radicals. OTCs can be photodegraded via dealkylation to produce low-substituted species and finally inorganic tin . Only DMT and DBT were detected in the reaction solutions under different light conditions with an initially increasing and then decreasing trend of concentrations, while the total tin concentrations continuously increased within the experimental period (Figure ).…”
Section: Resultsmentioning
confidence: 96%
“…OTCs can be photodegraded via dealkylation to produce lowsubstituted species and finally inorganic tin. 35 Only DMT and DBT were detected in the reaction solutions under different light conditions with an initially increasing and then decreasing trend of concentrations, while the total tin concentrations continuously increased within the experimental period (Figure 4). This confirmed that OTCs were concurrently photodegraded as they released from PVC microplastics.…”
Section: Environmental Science and Technologymentioning
confidence: 95%
“…In previous studies, HA were observed to either accelerate or inhibit the photodegradation of organic chemicals (24)(25)(26)(27). In some cases, the direction of the HA effect is dependent on the irradiation characteristics.…”
Section: Introductionmentioning
confidence: 96%
“…While several papers describe the environmental speciation of alkyltins due to physical and chemical agents [1, 3, 4, 2432], the data on their interactions with biological targets are rather scarce. A few reports point out the interactions of alkyltin with hemoglobin, H + -ATPase, the xenobiotic efflux pump PDR5, and the ion channel of the F-ATP synthase [3336].…”
Section: Introductionmentioning
confidence: 99%